Analysis of CyberMedia Ethical Code Violations on Online News Media - Ilfandy Imran, Ayub; Nur Atnan; Sheikh Yusuf Ahmed, Ismail (UPT Publikasi Ilmiah UNISBA, 2023)
The background of this research is a repeatedly ethical code violation by online media in Indonesia. Whereas on June 2020, Press Council warned the media, through a memorandum Number: 01/Seruan-DP/VI/202, to call every media, including online media, to work professionally in the news reporting about public issues. Therefore, the objective of this research was to find out the contributing factors of journalistic ethical code violations. In addition, this research also seeks to formulate solutions to minimize the violations. This research employed a constructive approach with a qualitative method. The data were collected through news observation in the three selected online media over the period of three months and through in-depth interviews with several informants. Several groups of informants are involved in this research, with the managers of the selected online media as primary informants. The secondary informants in this research are supervisory organizations or media observers verified by the Press Council, academicians/experts, and representatives of the Press Council. The research shows that the status of online media organizations influences the repeatedly journalistic ethical code violations. For example, verified online media by Press Council violates the ethical code more repeatedly than unverified online media.